(untitled) (Studia Prawnicze / The Legal Studies, 2010)
W świetle obowiązującej regulacji Kodeksu karnego z 1997 r. ocena prawnokarna zjawiska zaniechania udzielenia pomocy przez lekarza w sytuacji zagrożenia życia lub zdrowia człowieka ma charakter dwutorowy. Po pierwsze, zachowanie takie może stanowić formalne przestępstwo nieudzielenia pomocy z art. 162 § 1 k.k. Po drugie zaś, zaniechanie leczenia może być formą realizacji znamion przestępstwa skutkowego popełnionego przez zaniechanie, skierowanego przeciwko życiu lub zdrowiu, jeżeli zostanie ustalone, iż w konkretnych okolicznościach ciążył na konkretnym lekarzu prawny, szczególny obowiązek zapobiegnięcia skutkowi. W oparciu o przegląd piśmiennictwa stwierdzono, iż zagadnienia pojmowania prawnego, szczególnego obowiązku zapobiegnięcia skutkowi i źródeł obowiązku gwaranta w polskim prawie karnym zrodziły wiele wątpliwości. Praktyka sądowa w okresie obowiązywania kodeksów karnych z 1932 i 1969 r. sięgała do konstrukcji gwaranta bardzo rzadko i z wielką powściągliwością. Obecnie, pomimo wprowadzenia do kodyfi kacji karnej przepisu o odpowiedzialności za przestępstwo skutkowe popełnione w formie zaniechania przez osobę prawnie, szczególnie zobowiązaną do zapobiegnięcia skutkowi, również nie jest to konstrukcja nadużywana przez judykaturę. The present paper discusses the issue of criminal responsibility of a physician for an omission. In the light of the applicable provision of the Penal Code of 1997, the criminal-law evaluation of an omission to provide medical aid by a physician in the presence of a risk to life or health of a person is two-directional. First, such behavior may constitute the formal crime of not providing aid, under art. 162 (1) of the Penal Code. Secondly, an omission to provide treatment may meet the criteria of a consequential crime committed by omission, directed against the life or health of a person, if it found that in the specific circumstances the physician had a special legal duty to prevent the consequence. Based on the literature, it was concluded that the matters of understanding of the special legal duty to prevent a consequence and of the sources of the guarantor’s duty in the Polish criminal law raise numerous doubts. The original cause of the risk faced by the patient is the disease, which initially develops independently of the physician’s actions. By taking medical measures, the physician interferes with this process to prevent the negative effects, which would have taken place if such measures were not taken. A situation is also possible where the physician fails to take appropriate medical measures and to prevent the development of the disease. Without any treatment, or proper treatment, the patient’s disease becomes exacerbated and the risk to the patient’s life or health increases. The risk may reach a level that puts the patient’s life and health in imminent danger or may materialize as a purely physical change in the outside world when the patient dies or loses health. It must be underscored that even if the source of this risk is an element of the outside world, which is independent of the physician, since the first contact with the patient the doctor can influence the development of the disease. In the case of presence of a special legal duty to prevent a consequence, mentioned in art. 2 of the Penal Code, the physician, under criminal responsibility, must monitor the development of the disease and take steps that are appropriate in the specific case in accordance with the principles of medicine. The authors illustrated the principles of criminal responsibility of physicians for criminal omissions in connection with their professional practice using, as case studies, two cases in which enforceable verdicts were issued. The criterion for the selection of the cases to be studied was the person of the convict – a physician who committed a crime consisting, in its essence, in not taking life- and health-saving measures. The two selected cases concerned crimes whose source was a physician’s erroneous diagnosis. The literature indicates that in most such cases, where the essence of the crime is a physician’s medical error, it is not possible to convict the physician of causing consequences such as the death of a patient, disturbance of his or her bodily functions, or a health disorder. Because it is not possible to prove the connection between the physician’s improper behavior and the effect, taking the form of a purely physical change in the outside world, in practice the judicial system often qualifies the offense under art. 160 of the Penal Code.